ADVANTAGES OF ORGANIZING GEOGRAPHY LESSONS WITH THE USE OF VIDEO MATERIALS - Акишева, Майра; Боранкулова, Дина (Pedagogy and Psychology, 2022)
One of the main directions in the development of the geographical education system is the widespread use of information and communication technologies in the classroom. The use of ICT is aimed at developing information and communication competencies in students. Therefore, today the issues of formation of students' learning skills, information processing and critical comprehension, preparation for the reception of new knowledge through the use of information and communication technologies are relevant. In this regard, the task of the subject teacher is the daily use in the lessons of videos based on the topic, videos, TV programs, programs based on new information technologies. Using them, they can organize activities such as engaging students in creativity and interest in the subject, collecting information that can comprehensively describe the lesson, involving students in joint pair and group work. However, the collected data should be analyzed by the teacher in accordance with the age of the student, so that he can reveal a specific topic, does not exceed the time limit and does not get bored.